2019
DOI: 10.11591/ijeecs.v16.i1.pp208-215
|View full text |Cite
|
Sign up to set email alerts
|

A review on sensing-based strategies of interior lighting control system and their performance in commercial buildings

Abstract: <p>Artificial lighting consumed significant amount of electrical energy in commercial buildings. Therefore, intelligent control strategies are widely implemented to reduce the lighting energy consumption. This paper presents comprehensive review of the current sensing-based strategies (i.e. occupancy, daylight and mixed), sensors placement methods (i.e. occupancy and light) and factors affecting the performance of the lighting control strategies. Based on literature survey, the sensors placement methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In this regard, three sensor placement parameters need to be considered: (i) field of view (FoV), (ii) number and (iii) position. The FoV of each sensor cannot overlap between each other in order to reduce installation cost with the sensors quantity [35].Hence, strategically, the occupancy behaviour pattern and placement of the sensor should be studied well at the design stage before implementing the lighting control system in the building. This way the optimum balance between energy saving and user satisfaction can be achieved [34].…”
Section: Sensing-based Lighting Controlmentioning
confidence: 99%
“…In this regard, three sensor placement parameters need to be considered: (i) field of view (FoV), (ii) number and (iii) position. The FoV of each sensor cannot overlap between each other in order to reduce installation cost with the sensors quantity [35].Hence, strategically, the occupancy behaviour pattern and placement of the sensor should be studied well at the design stage before implementing the lighting control system in the building. This way the optimum balance between energy saving and user satisfaction can be achieved [34].…”
Section: Sensing-based Lighting Controlmentioning
confidence: 99%
“…Advances with respect to automated control systems are aimed at improving the management of the elements that allow the control of the crucial variables of the production process [19]. Automated management systems for the operation of work organs allow to improve the life cycle of the machines of the productive processes, guaranteeing to improve the productivity of the organizations [20].…”
Section: Introductionmentioning
confidence: 99%
“…A passive infrared (PIR) sensor can detect the presence of occupants (occupied or unoccupied) by monitoring their movements [12]. It is primarily used for performing occupancy control because of its cost‐effectiveness [3] [13]. However, References [14–17] have indicated that a PIR sensor cannot detect small movements such as those due to the arms and hands of occupants.…”
Section: Introductionmentioning
confidence: 99%
“…An occupancy lighting control, which is categorized as a sensorbased lighting control [3], is a popular and effective automatic lighting control. References [4][5][6][7] reported that compared with a light turned on continuously, the occupancy lighting control might reduce energy consumption by 20-46%.…”
Section: Introductionmentioning
confidence: 99%